An approach to Climate resilient agriculture farming system using Rice landraces collected from Tamil Nadu - Subiramaniyam, Ashok; Chandran, Sarankumar; Ramalingam, Kuttimani; Alagarswami, Senthil (Journal of Cereal Research, 2022)
A field experiment was conducted to determine the physiological performance of traditional rice landraces under water stress given at vegetative and reproductive stages. Drought is one of the serious threats on rice productivity. Traditional rice landraces shows substantial adaptability to drought so Six popular rice land races, namely Rascadam, Kothamalli sambha, Kaattu sambha, Kallundai, Kuliyadichan and Milagu sambha from Tamilnadu, India and two popular rice check varieties, namely IR64 (susceptible check), N22 (tolerant check) were used to study the physiological performance for drought tolerance. These genotypes were subjected to drought under field condition at Agricultural Research Station, Bhavanisagar, TNAU, Coimbatore. The crops were imposed with drought during vegetative and reproductive stages by withholding irrigation till the soil moisture reaches below 20 per cent. The experimental design for the trial was factorial randomized block design (FRBD). Photosynthetic rate, Stomatal conductance, Transpiration rate, Fv/Fm ratio were measured.